ANALISIS RASIO KEUANGAN LEMBAGA PERBANKAN (STUDI PADA BANK MANDIRI DAN BANK SYARIAH MANDIRI) - Ilma , Ailiya Silvia; Rahmawati , Ita; Sa’adah , Lailatus (Bisei : Jurnal Bisnis dan Ekonomi Islam, 2019)
This study aims to determine the financial performance of Bank Mandiri and Bank Syariah Mandiri based financial ratio analysis for five years namely 2013 to 2017. Type a descriptive study with a quantitative approach. The data are used data secondary from the annual financial statements published by the respective bank. Data analysis use financial ratio analysis and testing Independent Sample T-Test. The ratio used is the liquidity ratio which includes the Quick Ratio,Cash Ratio and LDR. The solvency ratio wihch includes DER and CAR. And profitability ratio that includes NIM, ROE, ROA and BOPO. The research result analysis if financial rations of Bank Mandiri and Bank Syariah Mandiri showed good result except in the profitability ratios and test results Independent Sample T-Tes showed that there wasn’t difference in financial performance between Bank Mandiri and Bank Syariah Mandiri when seen from the bank’s financial ratios.